Caffeine and Vision: Effects on the Eye - Audrey Yan; Antonio La Rosa; Preeti Patil Chhablani; Jay Chhablani (Türk Oftalmoloji Dergisi)
Caffeine, commonly found in coffee and tea, affects various aspects of eye health as it blocks adenosine receptors, impacting tear production, intraocular pressure, macular perfusion, and choroidal thickness. However, its connection with eye conditions like glaucoma and cataracts remains uncertain due to conflicting research findings. Some studies suggest potential benefits for cataracts, while others warn against frequent caffeine intake in glaucoma and surgical scenarios due to possible increases in intraocular pressure. Conflicting evidence also exists regarding its effects on dry eye, macular degeneration, myopia/hyperopia, diabetic retinopathy, retinopathy of prematurity, and central serous retinopathy. Caffeine does not seem to be a risk factor for dry eye, although studies have shown that caffeine may offer protection against wet age-related macular degeneration, and the metabolite 7-methylxanthine could be a more promising treatment for myopia. Moreover, caffeine can potentially cause tremors and might hinder surgical performance, especially in less experienced surgeons. Recommendations from experts vary, highlighting the need for further research to fully understand how caffeine affects the eye. Individuals genetically predisposed to glaucoma should be cautious due to the possibility of clinically significant elevations in intraocular pressure with caffeine consumption. For delicate procedures like microsurgery, where tremors can be detrimental, caution should be exercised with caffeine. This review underscores the importance of additional studies to provide clearer insights and prudent recommendations regarding caffeine’s impact on eye health.